Proteomics-based identification of novel factor inhibiting hypoxia-inducible factor (FIH) substrates indicates widespread asparaginyl hydroxylation of ankyrin repeat domain-containing proteins. - Cockman, M; Webb, J; Kramer, H; Kessler, B; Ratcliffe, P (2009)
Post-translational hydroxylation has been considered an unusual modification on intracellular proteins. However, following the recognition that oxygen-sensitive prolyl and asparaginyl hydroxylation are central to the regulation of the transcription factor hypoxia-inducible factor (HIF), interest has centered on the possibility that these enzymes may have other substrates in the proteome. In support of this certain ankyrin repeat domain (ARD)-containing proteins, including members of the IkappaB and Notch families, have been identified as alternative substrates of the HIF asparaginyl hydroxylase factor inhibiting HIF (FIH). Although these findings imply a potentially broad range of substrates for FIH, the precise extent of this range has been difficult to determine because of the difficulty of capturing transient enzyme-substrate interactions. Here we describe the use of pharmacological "substrate trapping" together with stable isotope labeling by amino acids in cell culture (SILAC) technology to stabilize and identify potential FIH-substrate interactions by mass spectrometry. To pursue these potential FIH substrates we used conventional data-directed tandem MS together with alternating low/high collision energy tandem MS to assign and quantitate hydroxylation at target asparaginyl residues. Overall the work has defined 13 new FIH-dependent hydroxylation sites with a degenerate consensus corresponding to that of the ankyrin repeat and a range of ARD-containing proteins as actual and potential substrates for FIH. Several ARD-containing proteins were multiply hydroxylated, and detailed studies of one, Tankyrase-2, revealed eight sites that were differentially sensitive to FIH-catalyzed hydroxylation. These findings indicate that asparaginyl hydroxylation is likely to be widespread among the approximately 300 ARD-containing species in the human proteome.